Fundamentos epistemológicos de los debates. - Darío Gómez-Arias, Rubén (Revista Facultad Nacional de Salud Pública)
This article aims to introduce the debate on epistemological paradigms. By epistemological paradigms, we mean those systems of rules that define the value of knowledge. The human capacity to elaborate images and representations of reality is a complex phenomenon. It is the result of biological conditions and of processes of social interaction that are gradually imposed to our ways of thinking and acting. "Paradigms" are systems of rules emerged from particular socioeconomic conditions. They pervade, often consciously, people's and groups' thinking, configuring the way they understand reality and act on it. In this introductory seminar, we will examine six of the paradigms that have influenced the most humanity's thinking: Idealism, Positivism, Dialectical Materialism, Historical Materialism, Postpositivism and Critically Oriented Inquiry. Additionally, we will examine the dynamics of popular knowledge and of ideologies, as models that are also imposed to people and groups' thinking. This seminar is considered essential to later understand how health and sicknesses have been understood throughout history.